Football-induced fatigue in hypoxia impairs repeated sprint ability and perceptual-cognitive skills - Pullinger, S. A.; Bradley, P. S.; Causer, J.; Ford, P. R.; Newlove, A.; Patel, K.; Reid, K.; Robertson, C. M.; Burniston, J. G.; Doran, D. A.; Waterhouse J. M.; Edwards, B. J. (Science and Medicine in Football, 2019)
Purpose:Investigate football-induced fatigue during hypoxia on RS and perceptual-cognitive skills. Methods: Ten semi-professional footballers underwent a control session (0-m) to quantify RS in a non-fatigued state; and three hypoxia sessions (0-m;1500-m;3000-m) examining RS and perceptual-cognitive skills for a given physical workload. The mean number of correct responses (%) for anticipation and decision-making accuracy were obtained at the 30-min mark of each half. HR, TC, RPE and %O2sat were measured during warm-up, football-induced fatigue and RS test. Results: HR, RPE and %O2sat were different between conditions (ES=0.44-6.13). RS were affected by football-induced fatigue for DC (4.8%;ES=0.68) and AV (5.5%;ES=0.79). In hypoxia, a 6.5% was found for DC, 6.3% for AV and 3.1% for PV at 1500-m compared to 0-m (P<0.05). Further significant changes of 12.8% DC, 12.8% AV and 6.2% PV (P<0.0005) were found at 3000-m compared to 0-m. More pronounced declines in perceptual-cognitive skills were found as altitude increased (5.0-12.5%;ES=1.17-2.41) and between halves (5.3-6.7%). Conclusion: The data demonstrates the RS test was sensitive to fatigue/hypoxia for a given physical load. Simulated matches in hypoxia revealed larger decreases, in RS and perceptual-cognitive skills, highlighting the need for optimal acclimatisation strategies, including physical and technical preparation, prior to playing at altitude.